Polar semivolatile organic compounds in biomass-burning emissions and their chemical transformations during aging in an oxidation flow reactor - Sengupta, Deep; Samburova, Vera; Bhattarai, Chiranjivi; Watts, Adam C.; Moosmüller, Hans; Khlystov, Andrey Y. (Atmospheric chemistry and physics, 2020)
Semivolatile organic compounds (SVOCs) emitted from open biomass burning (BB) can contribute to chemical and physical properties of atmospheric aerosols and also may cause adverse health effects. The polar fraction of SVOCs is a prominent part of BB organic aerosols, and thus it is important to characterize the chemical composition and reactivity of this fraction. In this study, globally and regionally important representative fuels (Alaskan peat, Moscow peat, Pskov peat, eucalyptus, Malaysian peat, and Malaysian agricultural peat) were burned under controlled conditions using the combustion chamber facility at the Desert Research Institute (DRI). Gas- and particle-phase biomass-burning emissions were aged in an oxidation flow reactor (OFR) to mimic 5–7 d of atmospheric aging. Fresh and OFR-aged biomass-burning aerosols were collected on Teflon-impregnated glass fiber filters (TIGF) in tandem with XAD resin media for organic carbon speciation. The polar fraction extracted with dichloromethane and acetone was analyzed with gas chromatography mass spectrometry (GC-MS) for 84 polar organic compounds – including mono- and dicarboxylic acids, methoxylated phenols, aromatic acids, anhydrosugars, resin acids, and sterols. For all these compounds, fuel-based emission factors (EFs) were calculated for fresh and OFR-aged samples. The carbon mass of the quantified polar compounds was found to constitute 5 % to 7 % of the total organic compound mass. A high abundance of methoxyphenols (239 mg kg−1 for Pskov peat; 22.6 % of total GC-MS characterized mass) and resin acids (118 mg kg−1 for Alaskan peat; 14.5 % of total GC-MS characterized mass) was found in peat-burning emissions (smoldering combustion). The concentration of some organic compounds (e.g., tetracosanoic acid) with a molecular weight (MW) above 350 g mol−1 decreased after OFR aging, while abundances of low-MW compounds (e.g., hexanoic acid) increased. This indicated a significant extent of fragmentation reactions in the OFR. Methoxyphenols decreased after OFR aging, while a significant increase (3.7 to 8.6 times) in the abundance of dicarboxylic acids emission factors (EFs), especially maleic acid (10 to 60 times), was observed. EFs for fresh and ratios from fresh-to-aged BB samples reported in this study can be used to perform source apportionment and predict processes occurring during atmospheric transport.